The Correlation among Parental Involvement, Reading Motivation and Reading Achievement of Senior High School Students - Maruli S, Bentar; Roni, Rusman; Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The purpose of this research was to find out the correlations among parental involvement, reading motivation and reading achievement.This research used correlation method. Total number of populations were 153 and sample were 60 students taken by simple random sampling technique. The instruments for collecting the data were questionnaire and test and analyzed by normality and linearity test. The result of the investigation described that (1) the correlationscoefficient between parental involvement and reading achievement rx1y=0.505 with r2= 0.255. r product moment shows that there was correlation between X and Y. Sig value was obtained sug 0.000 < 0.05, it shows that there was a significant correlation between parental involvement and reading achievement, (2) The result of rx2y = 0.514 with r2=0.265. The significant level was 0.000 < 0.05 it meant there was a significant correlation between reading motivation and reading achievement, (3) The result of rx2y = 0.604 with r2=0.365. The significant level was 0.000 < 0.05 it meant there was a significant correlation between parental involvement and reading motivation (4) the result of correlation among parental involvement, reading motivation and reading achievement were ryx1x2=0.569 with r2=324. It can be concluded that there are high correlations amongparental involvement, reading motivation toward reading achievement.